Efeito do jateamento com vidro niobofosfato na resistência de união de um adesivo em dentina afetada por cárie - Leal, Adriana Mara Araújo (2016)
Objectives: To evaluate the effect of airborne-particle abrasion with niobium phosphate bioglass (NbG) microparticles on the bond strength (µTBS) and longevity of an adhesive system to different dentin substrates. Methods and Materials: Caries-free molars were used in this study. The dentin surfaces were evaluated in three groups: (1) Control – Healthy Dentin; (2) Partial removal of carious tissue; (3) complete removal of carious tissue. Half the teeth in each group were submitted to airborne-particle abrasion with NbG microparticles (15s/1cm/5bar). After this, the adhesive Clearfil S3 was applied and composite buildups were constructed incrementally; and specimens were longitudinally sectioned to obtain bonded sticks (1.0 mm2) to be tested in tension (0.5 mm/min) immediately or after 6 months of storage in water. The fracture patterns were evaluated by stereomicroscope (40x) and then by scanning electron microscopy (SEM). The data were analyzed by the Kruskal-Wallis (post-hoc Dunn) and Mann-Whitney tests (α=0.05). Results: Healthy dentin showed the highest bond strength (µTBS). Airborne-particle abrasion with NbG increased the µTBS values in the complete caries removal group. The bond strength values in the 24-hr period were higher than those at 6 months. In the majority of the specimens the fracture mode was adhesive/ mixed. Conclusion: The authors concluded that airborne-particle abrasion on dentin with NbG particles increased the µTBS in the group in which carious dentin was completely removed.